"Trends Come and Go": Early Childhood Rural Special Education Teachers' Use of Reported Practices During Mathematics Instruction. (December 2021) - Peltier, Corey; Peltier, Tiffany K.; Hott, Brittany L.; Heuer, Andrew; Werthen, Taylor
Data suggest students are not meeting grade-level expectations in mathematics. If high-quality instruction is not provided, the inequitable outcomes observed in schools will be maintained. The goal of this study was to identify the frequency in which rural special education teachers (SETs) serving students in prekindergarten through third grade self-report using practices during mathematics instruction. A secondary focus was to investigate whether rural SETs differed in their reported use of practices compared with (a) suburban and urban SETs and (b) rural general education teachers. Data from 901 teachers serving students in prekindergarten through third grade were retained. Of this sample, 150 teachers identified as SETs in rural ( n = 55), suburban ( n = 50), and urban ( n = 45) schools. Results suggest teachers reported using research-based and unsubstantiated practices frequently. Rural SETs reported using research-based and unsubstantiated practices with similar frequency to urban SETs. Suburban SETs reported using explicit instruction more frequently than rural SETs.